Employing response surface approach for optimization of fusion characteristics in rigid foam PVC/clay nanocomposites. Issue 1 (18th June 2014) - Moghri, M.; Khakpour, M.; Akbarian, M.; Saeb, M.R.
Abstract : Employing response surface methodology, the fusion characteristics of poly(vinyl chloride)/nanoclay (NC) composite foams have been considered for optimization. To achieve the highest level of fusion (i.e., the maximum fusion factor as well as the minimum fusion time), different compounds were prepared based on response surface methodology in which various formulation parameters were changed. Through the choice of four design parameters at three selected levels, a total of 31 formulations were designed to probe the effects of different amounts of NC, blowing agent, processing aid, and internal lubricant. In addition, a mathematical model based on fusion characteristics was developed from experimental measurements. The chosen parameters resulted in varying effects on fusion factor and fusion time. Accordingly, the fusion factor was increased by increasing the NC and calcium stearate content, while a different trend was correct with foaming agent and processing aid. In addition, an opposite effect was observed for the fusion times of formulations. The observed behavior is discussed in terms of the effects of constituents on transformation of poly(vinyl chloride) grains, the level of NC exfoliation, and development of rigid interfaces. J. VINYL ADDIT. TECHNOL., 21:51–59, 2015. © 2014 Society of Plastics Engineers